2020
DOI: 10.1101/2020.07.03.20145060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health literacy in the general population in the context of epidemic or pandemic coronavirus outbreak situations: rapid scoping review

Abstract: BACKGROUND: Authorities responded with contact restrictions and other measures to the global spread of SARS-CoV-2. Health literacy (HL) has been linked to health outcomes and refers to the ability to access, understand, appraise and apply health information in order to make good health decisions. When restrictions are gradually lifted, individual HL becomes essential to control the pandemic and to prevent the resumption of these restriction, should infection numbers surge again. The aim of this rapid s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…The health literacy process produces knowledge and skills that enable a person to achieve health goals (Matterne et al, 2021). Health literacy is a form of knowledge, competence, and motivation to access, understand, assess, and apply health information in making the right decisions in health care, disease prevention, and health promotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health literacy process produces knowledge and skills that enable a person to achieve health goals (Matterne et al, 2021). Health literacy is a form of knowledge, competence, and motivation to access, understand, assess, and apply health information in making the right decisions in health care, disease prevention, and health promotion.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to acquire and access knowledge depends on understanding, time, and trust. At this stage, the ability to access information must balance in measuring the accuracy of the sources of information found (Matterne et al, 2021). If the source of information accessed and obtained is inadequate or has an inappropriate tendency, it will harm understanding and making decisions at the health literacy application stage.…”
Section: Accessmentioning
confidence: 99%
“…This study showed that the non-medical students had poor health literacy, including the knowledge on the Covid-19 and the level of compliance toward health protocol. Health literacy is closely related with healthy behavior [12] . Health information exposure is needed to improve health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…In another article in the present issue of PEC, Matterne et al review a large number of studies on health literacy and related phenomena in the context of corona virus outbreaks, including previous outbreaks as well as COVID-19 [ 6 ]. The authors found that only few studies explicitly referred to the concept of health literacy in their studies of health information seeking and other behaviors in a pandemic context.…”
Section: How Well Do People Understand Health Information?mentioning
confidence: 99%